Implementation of Prophetic Leadership in Green Waqf Management: A Comparative Case Study of Two Green Waqf Institutions in Indonesia - Muhammad Murtadha; Syahdatul Maulida (Faculty of Islamic Business and Management, 2025)
This research explores green waqf management, prophetic leadership implementation, and challenges faced by green waqf institutions in Indonesia, focusing on Hutan Wakaf Bogor and Greenwaqf. Using a qualitative descriptive case study approach, the findings reveal that Greenwaqf prioritizes renewable energy, while Hutan Wakaf Bogor emphasizes forest management. Both institutions have applied prophetic leadership values, though loyalty, exemplary behavior, accountability, transparency, and effective communication require further improvement. Key challenges include funding, regulatory frameworks, and nazhir resource development. The study recommends that stakeholders, particularly regulators, address these challenges by formulating supportive policies and enhancing nazhir guidance through prophetic leadership principles, fostering a stronger green waqf ecosystem.